La poeticità nel linguaggio medico, la scientificità del linguaggio letterario: Analisi di narrazioni su malattie - Maniowska, Katarzyna Maria (Moderna Språk, 2022)
In the present paper we focus on the comparison between medical language present in the narrative of some Italian writers: Antonio Tabucchi, Umberto Eco, Oriana Fallaci, Elena Ferrante, Dino Buzzati and fragments of medical reports that deal with the respective medical problems observed in the analysed novels/short stories: Il tempo invecchia in fretta, La misteriosa fiamma della regina Loana, Il cappello pieno di ciliege, La storia del nuovo cognome, Sette piani. With the comparative analysis of stylistically distant passages, we intend to indicate common points in the use of the Italian medical language both in the scientific and literary fields, as well as identify divergent linguistic aspects in the representations of this reality. We also intend to demonstrate the need to understand various narrative modes at different levels of specialized language. Despite different narrative modes, the essence of the phenomenon itself is not lost. There is also a common space in which meet various representations of the subjective truth that exists regardless of the language.